Assessment of the Dysautonomia Presence in Parkinson disease through Cardiovascular Signal Analysis - Alvarado Jalomo, S.; Alvarado Álvarez, N. A.; Dorantes Méndez, G. (Revista Mexicana de Ingenieria Biomedica, 2017)
The goal of this work is to assess and to compare the autonomic nervous system (SNA) response in Parkinson’s disease (EP) patients and healthy subjects in order to evaluate the possible dysautonomia presence. Electrocardiogram and photoplethysmography signals were acquired during the following maneuvers: rest, orthostatic change (Post-CP), controlled breathing (RC) and hyperventilation (Hip.). The signal processing was carried out by means of linear and no linear indices of heart rate variability (VFC), indices of pulse transit time (PTT) and baroreflex sensitivity (– index). Parkinson disease patients showed an attenuated sympathetic modulation mainly during Post-CP and the cardiovagal response resulted blunted during RC. Approximate entropy was significantly decreased in healthy subjects with respect to EP subjects during RC. In addition, the index – resulted in lower values in EP patients with respect to healthy subjects during the complete protocol, this result suggests that the baroreflex control in EP patients is blunted. However, is necessary to increase the number of subjects with the objective of determining levels of dysautonomia. The protocol designed to evaluate the dysautonomia presence in mexicans with EP through non invasive signals provides information about the SNA behavior.